The Impact of the Covid-19 Pandemic on the Well-Being and Diabetes Management of Adolescents With Type 1 Diabetes and Their Caregivers: A Scoping Review - Bassi, Giulia; Mancinelli, Elisa; Dell’Arciprete, Gaia; Salcuni, Silvia (Frontiers in Clinical Diabetes and Healthcare, 2022)
The Covid-19 pandemic and its related restriction measures might negatively impact diabetes management and well-being of adolescents with Type 1 Diabetes Mellitus (T1DM) and their caregivers. Accordingly, the present scoping review is aimed at mapping the literature in line with the question “How has the Covid-19 influenced diabetes management and well-being of adolescents with T1DM and their caregivers?”. A systematic search has been conducted through three academic databases. Studies carried out during the Covid-19 pandemic focused on adolescents aged between 10 and 19 years with T1DM and/or their caregivers were included. A total of 9 studies, performed between 2020 and 2021, have been identified. In particular, N = 305 adolescents with T1DM and N = 574 caregivers were considered. Overall, studies were not specific in reporting adolescents’ age, and only 2 studies were primarily focused on the adolescent population with T1DM. In addition, studies were mainly focused on evaluating adolescents’ glycemic control, which remained stable or has improved throughout the pandemic. Contrarily, psychosocial variables have been marginally considered. Indeed, only one study investigated adolescents’ diabetes distress, which remained stable from pre-to during post-lockdown, albeit improving among girls, specifically. As regards caregivers of adolescents with T1DM, studies showed mixed results concerning their psychological state during the Covid-19 pandemic. Prevention measures, which are aimed at supporting adolescents with T1DM during the lockdown, were considered by one study only, showing the favorable role of telemedicine during lockdown for adolescents’ glycemic control. Altogether, the current scoping review has identified many shortcomings of the available literature, which are given by the limited specificity of the age group considered and by the limited consideration of psychosocial variables, particularly their interplay with the medical ones.